Morphology of high‐latitude plasma density perturbations as deduced from the total electron content measurements onboard the Swarm constellation. Issue 1 (30th January 2017) - Park, Jaeheung; Lühr, Hermann; Kervalishvili, Guram; Rauberg, Jan; Stolle, Claudia; Kwak, Young‐Sil; Lee, Woo Kyoung
Abstract: In this study, we investigate the climatology of high‐latitude total electron content (TEC) variations as observed by the dual‐frequency Global Navigation Satellite Systems (GNSS) receivers onboard the Swarm satellite constellation. The distribution of TEC perturbations as a function of geographic/magnetic coordinates and seasons reasonably agrees with that of the Challenging Minisatellite Payload observations published earlier. Categorizing the high‐latitude TEC perturbations according to line‐of‐sight directions between Swarm and GNSS satellites, we can deduce their morphology with respect to the geomagnetic field lines. In the Northern Hemisphere, the perturbation shapes are mostly aligned with the L shell surface, and this anisotropy is strongest in the nightside auroral (substorm) and subauroral regions and weakest in the central polar cap. The results are consistent with the well‐known two‐cell plasma convection pattern of the high‐latitude ionosphere, which is approximately aligned with L shells at auroral regions and crossing different L shells for a significant part of the polar cap. In the Southern Hemisphere, the perturbation structures exhibit noticeable misalignment to the local L shells. Here the direction toward the Sun has an additional influence on the plasma structure, which we attribute to photoionization effects. The larger offset between geographic and geomagnetic poles in the south than in the north is responsible for the hemispheric difference. Key Points: Climatology of high‐latitude TEC perturbations as observed by Swarm reasonably agrees with that of CHAMP published earlier Irregularities in the NH are aligned with the L shell, strictly in the nightside auroral/subauroral region and loosely in the polar cap Perturbations in the SH are poorly aligned with the L shell, possibly due to the large offset between geographic and geomagnetic poles